Infants' response to a mobile phone modified still‐face paradigm: Links to maternal behaviors and beliefs regarding technoference. (4th June 2020) - Stockdale, Laura A.; Porter, Christin L.; Coyne, Sarah M.; Essig, Liam W.; Booth, McCall; Keenan‐Kroff, Savannah; Schvaneveldt, Emily
Abstract: Interruptions to parent–child interactions due to technology, or "technoference, " have been correlated with a host of negative child developmental outcomes. Yet, the influence of technoference on parent–infant interactions and infant behaviors has received less attention and more experimental work is warranted. For this study, parent–infant dyads ( n  = 227) completed a modified still‐face paradigm (SFP) using a mobile phone during the still‐face phase. Infant responses were coded for positive and negative affect, object and parent orientation, self‐comforting, and escape behaviors during the task. Results showed a robust still‐face effect, with infants displaying increased negative affect, decreased positive affect, increased self‐comforting, object orientation, and escape behaviors during the "still‐face" or phone distracted phase of the paradigm and frequently failing to return to baseline during the reunion phase. Older infants (older than 9 months) likewise demonstrated higher levels of negative affect across all three phases of the paradigm relative to younger infants (less than 9 months). Parent reports of technoference behavior were related to increased object orientation for younger infants. Parental technoference behaviors were also linked to more escape behaviors for younger infants and decreased object orientation in older infants during the still‐face portion of the SFP. Higher levels of technoference also appear to attenuate the negative emotional response of infants during still face. Results are discussed in relation to infants' increasing exposure to digital technology in the context of early relationships.